Probing the multitargeting potential of n-hexane fraction of Gongronema latifolium leaves in neurodegeneration via in vitro, GC-MS and in silico studies - Gideon A. Gyebi; Joseph C. Ejoh; Oludare M. Ogunyemi; Auza Moses Ibrahim; Ibrahim M. Ibrahim; Saheed O. Afolabi; Gabriel O. Anyanwu; Rotimi J. Ojo; Olalekan B. Ogunro; Badriyah S. Alotaibi; Gaber El-Saber Batiha (SpringerOpen, 2023)
Abstract Background Neurodegenerative disorders (NDDs) are associated with increased activities of brain acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and monoamine oxidase (MAO) as well as Aβ-amyloid (Aβ) neurotoxicity; therefore, they offer a therapeutic option for the treatment of NDDs such as Alzheimer's disease (AD). This study was aimed at identifying multi-targeting neurotherapeutics from Gongronema latifolium leaves using in vitro analysis, GC-MS profiling and computational methods. Results The n-hexane solvent partition fraction of the methanol extract of Gongronema latifolium leaf (HF) exhibited concentration-dependent inhibitory activities against acetylcholinesterase and butyrylcholinesterase but not against MOA in vitro. The GC-MS chemical profiling identified 17 phytochemicals from the HF; these were further screened against human AChE, BChE, β-secretase enzyme (BACE1) and amyloid-β (Aβ) fibrils using molecular docking, ensemble-based docking (EBD), molecular dynamics simulation (MDs) and binding free energy (BFG) coupled with predictive adsorption, distribution, metabolism, excretion and toxicity (ADMET) analysis. The lead phytochemicals (LPs) (dihydroactinidiolide and 1H-Indole-3-ethanamine), with mean binding energies (− 6.525 ± 0.895 and 6.475 ± 0.985; − 6.833 ± 0.461 and − 6.466 ± 0.577; − 6.2 ± 0.845 and − 5.95 ± 0.353 kcal/mol) exhibited multi-target binding tendencies to the catalytic residues of hAChE, hBChE and hBACE1, in addition to hAβ fibril-disruptive tendencies (− 6.325 ± 0.545 and − 5.95 ± 0.353 kcal/mol), respectively. These results corroborated the initial molecular docking and BFG computations. The lead phytochemical-protein complexes were stable during the period of MDs. The LP presented favorable drug-likeness and ADMET properties coupled with the capacity to traverse the BBB. Conclusion Dihydroactinidiolide and 1H-Indole-3-ethanamine, in part or in synergy, are identified as neurotherapeutic constituents of Gongronema latifolium that may have been responsible for the ethnopharmacologically reported neurotherapeutic activities of the leaf, and hence they are suggested as potential drug candidates that can be useful for managing or treating neurodegenerative disease such as Alzheimer's disease, subject to further investigation.